1991
DOI: 10.1007/bf00994418
|View full text |Cite
|
Sign up to set email alerts
|

2,2?-OXO-1,1?-azobenzene: Selective toxicity of rye (Secale cereale L.) allelochemicals to weed and crop species: II

Abstract: Three allelochemicals from rye or its breakdown products were evaluated for activity on garden cress (Lepidum sativum L.), barnyardgrass [Echinochloa crus-galli (L.) Beauv.], cucumber (Cucumis sativus L.), and snap bean (Phaseolus vulgaris L.). 2,4-Dihydroxy-1,4(2H)-benzoxazin-3-one (DIBOA), 2(3H)-benzoxazolinone (BOA), and 2,2'-oxo-1,1'-azobenzene (AZOB) were all applied singly at 50, 100, and 200 ppm and in two- and three-way combinations each at 50 and 100 ppm. AZOB at 100 and 200 ppm produced 38-49% more i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
36
0

Year Published

1998
1998
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(38 citation statements)
references
References 18 publications
2
36
0
Order By: Relevance
“…However, DIBOA is unstable with a half-life of 1 day or less in an aqueous solution (pH 5-7) at room temperature and rapidly hydrolyzes into the less toxic BOA (Bredenberg et al, 1962, in Fomsgaard et al 2004). BOA (benzoxazolin-2(3H)-one), in turn, can be broken down by microbes into the more toxic allelochemical 2-amino-phenoxazin-3-one (APO) (Chase et al 1991;Gagliardo and Chilton 1992). Because of the difference in toxicity of the subsequent hydroxamic acid derivatives and the dependence of their half-lives on many factors, including the prevailing temperature and soil moisture, temporal patterns of phytotoxicity will be difficult to predict.…”
Section: Discussionmentioning
confidence: 99%
“…However, DIBOA is unstable with a half-life of 1 day or less in an aqueous solution (pH 5-7) at room temperature and rapidly hydrolyzes into the less toxic BOA (Bredenberg et al, 1962, in Fomsgaard et al 2004). BOA (benzoxazolin-2(3H)-one), in turn, can be broken down by microbes into the more toxic allelochemical 2-amino-phenoxazin-3-one (APO) (Chase et al 1991;Gagliardo and Chilton 1992). Because of the difference in toxicity of the subsequent hydroxamic acid derivatives and the dependence of their half-lives on many factors, including the prevailing temperature and soil moisture, temporal patterns of phytotoxicity will be difficult to predict.…”
Section: Discussionmentioning
confidence: 99%
“…When BOA and its related products are exuded as active plant metabolites from the roots into the soil, they can be absorbed and translocated into other crop plants to cause physiological disturbances that can even include declines in crop yields (17). This phenomenon has been demonstrated in various test plants, such as Lactuca sativa (18), Lepidium sativum (19), Avena sativa (20) and Cucumis sativus (21). Therefore, reducing the inhibitory effect of BOA derivatives on economic crops through the use of microbial metabolic processes is imperative.…”
mentioning
confidence: 99%
“…Seed germination assays (Barnes & Putnam, 1987;Pérez, 1990;Chase et al, 1991) showed that species with small seeds were more sensitive, and hence were inhibited more than larger seeded species when exposed to similar concentration of the allelochemicals. Seedling parameters also had no significant reduction.…”
Section: Discussionmentioning
confidence: 99%